Pola Pertumbuhan Pendederan Ikan Nila (Oreochromis Niloticus) Pada Keramba Jaring Tancap Kolam Tanah Di Rengasdengklok, Karawang, Jawa Barat - Wahjudi Poerwanto; Donatus Haryadi Guntur Prabowo; Maria Goreti Eny Kristiany; Catur Pramono Adi; Zaskia Khansa Salviadi; Liliek Soeprijadi (SINTA Journal (Science, Technology, and Agricultural), 2025)
This study was conducted to understand the growth pattern of tilapia (Oreochromis Niloticus) when cultivated in earthen ponds with a fixed net cage system. The location of the practice is at PT. Suri Tani Pemuka Rengasdengklok, Karawang, West Java. The main focus of this activity is to see the relationship between the length and weight of fish during the maintenance period, as well as to assess the comparison of the growth of length and weight of fish for each sampling and the survival rate (SR) of fish. From the results of the observation, it is known that the b value in the analysis of length and weight is 0.72220, which indicates that growth is negative allometric - meaning that fish grow faster in length than in weight. In addition, the survival rate of fish reached 76.4%, which is quite high and indicates that the maintenance conditions are running quite well. Fixed net cages (KJT) are a fish maintenance method that has several advantages, namely it can avoid water predators and is able to limit the circulation of fish so that it facilitates harvesting, but the growth rate is still influenced by other factors including water quality and feed. With this method, fish can grow more safely and optimally. It is hoped that the results of this practice can be an illustration and reference for other cultivators who want to apply similar methods.